h2⋅r2=162

Divide each term in h2⋅r2=162 by r2.

h2⋅r2r2=162r2

Cancel the common factor of r2.

Cancel the common factor.

h2⋅r2r2=162r2

Divide h2 by 1.

h2=162r2

h2=162r2

Raise 16 to the power of 2.

h2=256r2

h2=256r2

Take the square root of both sides of the equation to eliminate the exponent on the left side.

h=±(256r2)12

Simplify the right side of the equation.

Apply the product rule to 256r2.

h=±25612(r2)12

Simplify the numerator.

Rewrite 256 as 162.

h=±(162)12(r2)12

Apply the power rule and multiply exponents, (am)n=amn.

h=±162(12)(r2)12

Cancel the common factor of 2.

Cancel the common factor.

h=±162(12)(r2)12

Rewrite the expression.

h=±16(r2)12

h=±16(r2)12

Evaluate the exponent.

h=±16(r2)12

h=±16(r2)12

Simplify the denominator.

Multiply the exponents in (r2)12.

Apply the power rule and multiply exponents, (am)n=amn.

h=±16r2(12)

Cancel the common factor of 2.

Cancel the common factor.

h=±16r2(12)

Rewrite the expression.

h=±16r

h=±16r

h=±16r

Simplify.

h=±16r

h=±16r

h=±16r

The complete solution is the result of both the positive and negative portions of the solution.

First, use the positive value of the ± to find the first solution.

h=16r

Next, use the negative value of the ± to find the second solution.

h=-16r

The complete solution is the result of both the positive and negative portions of the solution.

h=16r

h=-16r

h=16r

h=-16r

h=16r

h=-16r

Solve for h h^2*r^2=16^2